INVESTIGATION OF GENETIC DIVERGENCE IN CHICKPEA (CICER ARIETINUM L.) GENOTYPES - SACHIN D. PARHE; P. N. HARER; D. R. NAGAWADE (The Bioscan, 2014)
An experiment with fifty one genotypes of Chickpea carried out to study the nature and magnitude of genetic divergence using Mahalanobis’s D2 Statistics, in randomized block design with two replications. The data for eight important quantitative traits recorded from the genotypes raised. The fifty one Chickpea genotypes were grouped into five clusters. Cluster I was largest with forty genotypes followed by cluster II with eight genotypes. The maximum inter-cluster distance was observed between cluster I and V, followed by cluster II and V suggesting that the genetic architecture of the genotypes in one cluster differ entirely from those included in other clusters. Three characters viz. 100 seed weight, No. of pods per plant and Days to 50% flowering contributed maximum in manifestation of genetic diversity. Seed yield plant-1 had maximum Phenotypic and Genotypic Coefficient of Variation (PCV and GCV), followed by 100 seed weight. High magnitude of heritability (broad sense) was recorded for 100 seed weight. High heritability coupled with high genetic advance was observed for number of pod per plant, 100 seed weight, Days to 50% flowering and Plant height suggesting that, the role of additive gene effect and possibilities of achieving high genetic progress through selection. The genotypes IC-270936, IC487323, IC-350889, Vishal, Digvijay, IC-442831, IC-268927, IC-327656, IC-299779, EC-490044 and IC-269004 were identified as genetically diverse parents, which can be utilized for future crop improvement programme in Chickpea.